Clinical Follow-up of a Patient with Muscle Weakness During the Postoperative Intensive Care Period - Mustafa Deniz; Ali Rıza Kağnıcı; Bilge Banu Taşdemir; İbrahim Kurt (Galenos Yayinevi, 2021)
The patient underwent intensive care after an acute abdominal surgery due to intestinal perforation. The patient was examined for postoperative muscle weakness, and the differential diagnosis was studied. Guillain-Barré syndrome is an acute inflammatory demyelinating polyneuropathy. Infection, surgery, and transplantation have been cited in its etiology. History, clinical examination and follow-up, laboratory tests, and electrophysiological studies are important in its diagnosis, as well as differential diagnosis. Intravenous immunoglobulin and plasmapheresis are the mainstays of care, and supportive care is important for long-term treatment. In this case report, an intensive care unit approach was discussed, in which the surgical paradigm and gastrointestinal stromal tumor were thought of as a rare paraneoplastic complication.